2019
DOI: 10.1021/acs.iecr.8b04723
|View full text |Cite
|
Sign up to set email alerts
|

Volatility of Deep Eutectic Solvent Choline Chloride:N-Methylacetamide at Ambient Temperature and Pressure

Abstract: Common organic volatile solvents would volatilize in air, thus causing air pollution and harming human health. Deep eutectic solvents (DESs) are one type of the green solvents with low volatility, deemed as the new solvents of the 21st century. Previous investigation showed that the DESs would undergo volatilization at high temperature and/or vacuum pressure. However, how DESs volatile at ambient temperature and pressure is unknown. Here the volatilization of DESs in air at ambient temperature and pressure was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…They are a eutectic mixture composed of Lewis or Brönsted acid (hydrogen bond donor commonly defined as HBDs) and bases in the form of salts (hydrogen bond acceptors commonly defined as HBAs), that can contain different types of anions and cations. In Figure 4, the most common hydrogen bond donors and hydrogen bonds acceptors are reported [49,50]. The reaction between crotonaldheyde 67a and (Z)-N-benzylidene-1-phenylmethanamine oxide 66 was selected to study the effects of all organocatalysts and ionic liquids, comparing the results with those obtained in classical conditions (CH 2 Cl 2 ; 5 • C; 4 die).…”
Section: Deep Eutectic Solvents (Des)mentioning
confidence: 99%
See 2 more Smart Citations
“…They are a eutectic mixture composed of Lewis or Brönsted acid (hydrogen bond donor commonly defined as HBDs) and bases in the form of salts (hydrogen bond acceptors commonly defined as HBAs), that can contain different types of anions and cations. In Figure 4, the most common hydrogen bond donors and hydrogen bonds acceptors are reported [49,50]. The reaction between crotonaldheyde 67a and (Z)-N-benzylidene-1-phenylmethanamine oxide 66 was selected to study the effects of all organocatalysts and ionic liquids, comparing the results with those obtained in classical conditions (CH 2 Cl 2 ; 5 • C; 4 die).…”
Section: Deep Eutectic Solvents (Des)mentioning
confidence: 99%
“…They are a eutectic mixture composed of Lewis or Brönsted acid (hydrogen bond donor commonly defined as HBDs) and bases in the form of salts (hydrogen bond acceptors commonly defined as HBAs), that can contain different types of anions and cations. In Figure 4, the most common hydrogen bond donors and hydrogen bonds acceptors are reported [49,50]. This phase, composed of two or more components, generally does not form new chemical compounds through covalent bonds, but the main bonding interactions of non-covalent nature are: Hydrogen interactions, α-hole interactions, π-hole interactions, and other two recently discovered as ĸ-hole and µ-hole interactions [51].…”
Section: Deep Eutectic Solvents (Des)mentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have indicated that DESs has minimal or negligible volatility relative to traditional organic solvents. However, recently, Chen et al [ 41 ] reported the volatilization of ChCl: N -methylacetamide (1:6) DES even at room temperature and pressure. Another study conducted by the same group [ 42 ] found that the polyethylene glycol (PEG)-based DESs showed volatilization under the same conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although DESs are considered to have negligible vapor pressure, some systems will lose weight significantly at room temperature. [16] The internal reason is that these systems contain volatile components,a nd the essence of this process is volatilization rather than decomposition. The interaction sites in the system can be determined by analyzing the weightlessness process.…”
mentioning
confidence: 99%